Functional cardiac MRI in preterm and term newborns. Issue 2 (21st October 2010) - Groves, Alan M; Chiesa, Gaia; Durighel, Giuliana; Goldring, Stephen T; Fitzpatrick, Julie A; Uribe, Sergio; Razavi, Reza; Hajnal, Jo V; Edwards, A David
Abstract : Objective: To use cardiac MRI techniques to assess ventricular function and systemic perfusion in preterm and term newborns, to compare techniques to echocardiographic methods, and to obtain initial reference data. Design: Observational magnetic resonance and echocardiographic imaging study. Setting: Neonatal Unit, Queen Charlotte's and Chelsea Hospital, London, UK. Patients: 108 newborn infants with median birth weight 1627 (580–4140) g, gestation 32 (25–42) weeks. Results: Mean (SD) flow volumes assessed by phase contrast (PC) imaging in 28 stable infants were left ventricular output (LVO) 222 (46), right ventricular output (RVO) 219 (47), superior vena cava (SVC) 95 (27) and descending aorta (DAo) 126 (32) ml/kg/min, with flow being higher at lower gestational age. Limits of agreement for repeated PC assessment of flow were LVO ±50.2, RVO ±55.5, SVC ±20.9 and DAo ±26.2 ml/kg/min. Mean (SD) LVO in 75 stable infants from three-dimensional models were 245 (47) ml/kg/min, with limits of agreement ±58.3 ml/kg/min. Limits of agreement for repeated echocardiographic assessment of LVO were ±108.9 ml/kg/min. Conclusions: Detailed magnetic resonance assessments of cardiac function and systemic perfusion are feasible in newborn infants, and provide more complete data with greater reproducibility than existing echocardiographic methods. Functional cardiac MRI could prove to be a useful research technique to study small numbers of newborn infants in specialist centres; providing insights into the pathophysiology of circulatory failure; acting as an outcome measure in clinical trials of inotropic intervention and so guiding clinical practice in the wider neonatal community.